A context-aware service framework for mobile ad hoc networks. (2016) - Chen, Tzung-Shi; Wang, Neng-Chung; Yu, Gwo-Jong; Chen, Hsin-Ju
A mobile ad hoc network (MANET) is established by mobile devices without relying on a fixed infrastructure. MANETs usually have attractive applications with regard to intelligent transportation systems and digital life. In this paper, we propose a service framework for supporting context-aware environments in MANETs. A virtual overlay network and two novel approaches within this framework have been addressed to significantly improve the efficiency of the data delivery. The surrounding context of mobile nodes is used to determine our strategy adopting push-based or pull-based approaches. When a real-time event occurs in a node, a push-based approach is adopted to disseminate urgent messages to neighbouring nodes. On the contrary, a pull-based approach is adopted and a virtual backbone, namely a segment-tree virtual network, is constructed to conduct contextual information. Simulation results show that our proposed approach outperforms the existing publish/subscribe approach.